The Pengaruh Kebijakan Dividen, Kebijakan Hutang, Dan Return On Equity Terhadap Nilai Perusahaan Studi Kasus Pada Perusahaan Subsektor Industri Dasar Dan Kimia Yang Terdaftar Di Bei Tahun 2021 - Lauli, Chrisna Yosefine; Hapsari, Nesti (Peneliti.net, 2024)
The study aims to illustrate and share information data on how a company's values might be measured in three key aspects: dividends, debt policies, and profitability policies. The method used in this study is berganda linear analysis. In pandemics such as today, some companies, especially in certain sectors, may experience a decline in profits. However, many companies have also changed their policies to keep business afloat in the pandemic. The study focuses on basic industrial and chemical subsectors by using their financial statements in 2018 to 2022. What this study has discovered is that in basic industrial and chemical subsectors, debt policies have no effect on corporate values, while dividends and profitability policies have an impact on corporate values. Researchers hope that the results of this study will benefit companies, the general public, and future researchers.